A multiscale procedure for solving nonlinear mechanical problems in heterogeneous media - Alkmim, Nasser Samir (2019)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Civil e Ambiental, 2019.